QUANTITATIVE ESTIMATION OF MAGNESIUM CARBONATE IN PAN MASALA AND GUTKA - Priyambada, Pandey; Anju, Goyal (International Journal of Current Pharmaceutical Research, 2018)
Objective: The objective of present study is to detect and quantitatively estimate Magnesium Carbonate, a potential carcinogen used for its anti-caking property in various brands of Pan Masala and Gutka by the simple, economic and effective method. Methods: The water-soluble extract of various brands of Pan Masala and Gutka was prepared by a wrist action rotary shaker for 60 min. The extract was filtered, and the filtrate was titrated against 0.1N EDTA using Eriochrome Black T indicator at pH 10 and using Murexide indicator at pH 12. Results: The presence of Magnesium Carbonate was found to be less than 2% in all brands of Pan Masala and less than 3% in all brands of Gutka samples used in the analysis. Conclusion: There is Magnesium Carbonate used in all brands of Pan Masala and Gutka used in the present study.